2012
DOI: 10.1177/0971685812454486
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Begging: A Social Stigma—An Indian Perspective

Abstract: The economic growth in India is quite visible through infrastructural and industrial growth in metros but the same is overshadowed by the poor plight of beggars in these cities. This article addresses the living conditions of the beggars and their awareness about the various government policies. The study gives an insight into the economic status of beggars and answers why people go for begging. The solution calls for a comprehensive programme and reorientation of the existing programmes. We often read and hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 1 publication
0
6
0
1
Order By: Relevance
“…Weekly income was typically USD 20–70 (Kemp, 1997; Sailaja & Rao, 2016), though could be as much as USD 262.95 (Dean, 1999). Several studies indicate that monthly income for begging is between USD 150 and 500 (Bose & Hwang, 2003; Debeck et al, 2007; Mansour, 2017; Poremski et al, 2015), it was rarely less than this amount (Malik & Roy, 2012). Two studies found that monthly income was USD 697–2,093 (Gaga, 2015; Rahmalia & Zulyadi, 2019), though the sample sizes are unclear for both of these studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Weekly income was typically USD 20–70 (Kemp, 1997; Sailaja & Rao, 2016), though could be as much as USD 262.95 (Dean, 1999). Several studies indicate that monthly income for begging is between USD 150 and 500 (Bose & Hwang, 2003; Debeck et al, 2007; Mansour, 2017; Poremski et al, 2015), it was rarely less than this amount (Malik & Roy, 2012). Two studies found that monthly income was USD 697–2,093 (Gaga, 2015; Rahmalia & Zulyadi, 2019), though the sample sizes are unclear for both of these studies.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the wide range of incomes that some panhandlers receive (Conroy, 2001; Goldstein, 1993; Luckenbach & Acosta, 1993; Wamstad, 2007), sources that rely on small samples are susceptible to having extreme values compared to studies that report average values among larger samples (e.g., Bose & Hwang, 2003; Lee & Farrell, 2003; Lein et al, 2008). Similarly, considerable variation exists regarding how income is reported with some studies providing a range (Goldberg, 1995; Jamil et al, 2019), varying measures of central tendency (Bose & Hwang, 2003; Conroy, 2001; Lee & Farrell, 2003), or as an ordinal variable (Malik & Roy, 2012; Mansour, 2017). The decision was made to include all of these studies despite the inevitable challenges raised by comparing such diversely conducted research.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such conditions require education and skills. There are studies that state that the provision of education will be a solution for the poor, namely the homeless and beggars [26].…”
Section: Education and Skillsmentioning
confidence: 99%
“…While some studies dealing with begging, e.g. Williams and Windebank (2002), believe that begging is a survival activity practiced by those who lack alternative income-generating opportunities, and that the income from begging is considerably lower than the income from formal work, it seems that begging has turned for some beggars into something of a lucrative profession (Malik & Roy, 2012), and that mendicancy for those who beg in tourist areas can be remarkably profitable. This is evident from Gossling's et al (2004, p. 140) study in Antananarivo, Madagascar which found that 62 percent of the tourists interviewed had given money or made non-monetary donations to street children, and of those who did not, a considerable proportion stated that they did so because they believed that their donations would encourage begging and have negative social consequences in the long run.…”
Section: Begging and Tourismmentioning
confidence: 99%